Village Baseline Study: Site Analysis Report for Lawra – Jirapa, Ghana (GH0108) - Onyango, Leah; Iddrisu Y; Mango, Joash; Kurui, Zena; Wamubeyi, B.; Bawayelaaza Nyuor A; Naab, Jesse B. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2012)
The village baseline study of Doggoh village in the CCAFS benchmark site Jirapa-Lawra in Ghana took place from 26th to 28st July 2011. Focus group discussions were conducted separately for men and women. Doggoh village is located in a Sudan Savannah characterized by a considerable tree population, and the farming system it practices involves cultivation among trees. Land is cultivated by individuals but owned and administered communally through a traditional system of local chiefs. The average land productivity is low and the community can only produce enough to feed themselves for 3 months a year, resulting in the need to seek food from other sources for 9 months of the year. To survive, people depend on remittances. Trees are communally managed with community sanctions against those who break the accepted practice. Nonetheless, the sale of wood fuel is putting pressure on the tree population. There is evidence of degradation on the landscape where vegetation has been removed and there is bare soil. The community relies on boreholes for their domestic water supply and take for granted the value of wetlands and the rivers, which remained effectively unmanaged. The participants identified 22 organisations in the village, including 12 operating beyond the locality, 3 functioning within the locality and 7 operational within the community. Seventeen organisations contribute to food security, and other 14 encourage natural resource management. Organisations and radio are the most important sources of information.